AB1137 QUANTIFYING KNEE JOINT EFFUSIONS WITH CLINICAL TESTS, MUSCULOSKELETAL ULTRASOUND AND SYNOVIAL FLUID ASPIRATION: A PROSPECTIVE COHORT STUDY. (June 2019) - Silva, Thilinie De; Pham, Chris; Rischin, Adam; Marshall, Kim Le; Vogrin, Sara; Leung, Albert; Lim, Keith
Abstract : Background: Aspiration of knee joint effusions is an integral diagnostic and therapeutic intervention in many rheumatologic diseases. Clinical examination has traditionally involved tests including the "patella tap" or "bulge test". The accuracy of these tests for determining effusion presence and size is not well established. Musculoskeletal ultrasound (MUS) is considered better for identification and quantification of knee effusions. Objectives: To investigate the correlation between both clinical examination and MUS to aspirated knee effusion volume. Methods: We performed a prospective cohort study of 37 osteoarthritis patients with symptomatic knee effusions. Clinical assessment with patella tap, bulge test and knee circumference measurement were carried out. MUS was used to measure effusion depth in the suprapatellar, lateral and medial parapatellar views. All knee effusion aspirations were performed by the same experienced clinician using a consistent, lateral approach. Linear regression analysis was used to assess correlations between clinical tests, MUS and aspiration volume. Results: In patients with >3ml of fluid aspirated, patella tap and bulge test were positive in 67% and 80% respectively. The positive predictive value for bulge test was 80%. Where larger volumes were aspirated (i.e. >10ml), patella tap and bulge test were only positive in 52% and 65% respectively. There was a significant correlation between the measured circumference of the index and non-index knee and aspiration of fluid (coefficient=5.6, p=0.007). The relationship between fluid depth on MUS and aspirated volume showed a trend towards statistical significance, with a depth of 1mm equating to 1.57 ml of fluid (coefficient=1.57, p=0.06). Conclusion: This pilot study demonstrates that a positive patella tap or bulge test is moderately predictive of knee effusion volume. However, this association is weaker when larger knee effusions are present. MUS showed promise at accurately predicting knee effusion volume. A larger study is underway to assess this relationship further. Disclosure of Interests: Thilinie De Silva: None declared, Chris Pham: None declared, Adam Rischin: None declared, Kim Le Marshall: None declared, Sara Vogrin: None declared, Albert Leung: None declared, Keith Lim Consultant for: Advisor for role of hepatitis and TB in Cimzia, UCB, Speakers bureau: Role of biological in pregnancy UCB